Wet season supplementation of West African Dwarf (WAD) goats in the subhumid zone of Nigeria - Ikwuegbu, O.A.; Tarawali, G.; Kaufmann, Ralph R. von (Nigeria Ministry of Agriculture and Water Resources, 1993)
This paper determines the productivity of West African Dwarf goats in the subhumid zone of Nigeria and compares the relative merits of alternative wet season feed regimes namely; tethering goats on natural pasture, tethering goats on leguminous pasture and free grazing goats on leguminous pasture. The results presented represent the animal studies component for the one year (1989/1990) and was conducted in the Ganawuri area of plateau state. Goats were monitored and recorded for weight, births, sales and deaths etc every 2 weeks. Dry matter yield and botanical composition of pasture were determined.